Martina Chapanay and the de-construction of an imaginary (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2020)
This article analyzes the imaginary built on Martina Chapanay, a recognized bandolier who traveled through rural areas of the west center of present-day Argentina in the 19th century. Passages of his life have been passed down from generation to generation, communicating knowledge and cultural meanings, which as such have been disrupted over time. What I maintain here is that what endures in the collective memory is the re-meaning of these narratives in the written texts. The authors of the first literary works on Martina represented her with certain archetypes of gender, race and class contained in the hegemonic discourse of her own time. From the review of the imaginary built on it, from the perspective of gender studies and decolonial perspectives, I reflect on identities and ways of life silenced and denied by power.
Keywords: Imaginary; Symbols; Decolonial; Woman; Gender